Going through a rough patch: Oral adverse effects of secukinumab. (18th October 2021) - Yogarajah, Sangeetha; Mahendran, Krishantini; Barker, Jonathan; Setterfield, Jane; Carey, Barbara
Abstract: Chronic hyperplastic candidiasis (CHC) clinically presents with white plaques involving the post‐commissural buccal mucosa and less frequently, the tongue. Common risk factors include xerostomia, smoking, post‐chemotherapy or radiotherapy, antibiotic use, vitamin deficiency and immunosuppression. Here, we present a case of CHC secondary to secukinumab. A 38‐year‐old man presented with a 6‐month history of asymptomatic white plaques involving the lateral tongue and buccal mucosa. The medical history included chronic plaque psoriasis controlled with secukinumab 300 mg monthly, initiated 6 months prior to presentation. Intraoral examination revealed dense homogenous keratosis involving the right and left posterior lateral tongue and posterior buccal mucosa. Histopathological examination was consistent with chronic hyperplastic candidiasis. Special stains for fungal hyphae were positive. In situ hybridization for EBV were negative. Serology was negative for HIV. He was managed with fluconazole 100 mg daily for 1 week and placed on a prophylactic antifungal regime of chlorhexidine 0.2% mouthwash to reduce overall Candida load; however, the white plaques remained unchanged. He subsequently discontinued secukinumab and switched to certolizumab, resulting in complete resolution of oral candidiasis. In psoriasis, dysfunction in the cytokine pathway results in excessive production of IL‐17A. Secukinumab, a next‐generation anti‐IL‐17A biologic, is being used more commonly to manage moderate–severe plaque psoriasis. Clinicians should be aware of the risk of development of candidiasis as a potential complication of secukinumab due to the concurrent role of IL‐17 in innate and adaptive immunity against Candida. Early recognition of oral Candida lesions with diagnostic biopsy is paramount to exclude dysplasia.